Humanitarian Intervantion: The Principle of Responsibility to Protect (R2P) - Muhammad Zahrul Anam (Universitas Muhammadiyah Yogyakarta, 2015)
This article describes the notion of the Responsibility to Protect (R2P) as a branch of humanitarian intervention. This approach emerges to immediately respond atrocities of innocent people due to political persecution taking place in a state. R2P allows external power in the form of the military operation to prevent casualties of citizen. The opponents of R2P argue that it contradicts with the non-intervention principle based on state-sovereignty. However, the proponents of this approach believe that human security and rights should be beyond of state. It is assumed that R2P remains relevant to completely stop either state violation over its citizen or armed conflict within civil war. The discussion of this paper therefore compress the notion of Humanitarian Intervention and the grounds of Humanitarian Intervention, which concerns mainly on the debate the Responsibility to Protect of what is nature of this approach, of who are authorized actors in charge as well as of how it should be implemented.